COVID-19: Failure of the DisCoVeRy Clinical Trial, and Now–New Hopes? - Jean Jacques Vanden Eynde (Pharmaceuticals, 2021)
The DisCoVeRy clinical trial aimed at the evaluation of four treatments for patients suffering from severe to critical COVID-19: Hydroxychloroquine, eventually associated with azithromycin; the combination lopinavir/ritonavir; the combination with the addition of interferon β-1a; remdesivir. The trial was discontinued due to the lack of positive results. Meanwhile, many other potential options have been considered either to target the virus itself, the interactions with the host cells, or the cytokine storm frequently observed during the infection. Several of those options are briefly reviewed. They include vaccines, small molecules, antibodies, and stem cells.